MOTIVASI INDIA MENJALIN KERJASAMA EKONOMI DENGAN NEGARA-NEGARA AFRIKA - Rinaldi "; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Africa is the poorest continent with economic growth is relatively slow compared to other countries. This is because since the beginning of its independence from western colonialism, Africa was hit by the prolonged conflict. Due to poverty and security, Western nations are reluctant to invest and provide economic assistance to African countries. Western countries saw Africa as a field of conflict and human rights violations. In contrast to Western countries, India actually investing heavily in Africa. Indian direct investment in Africa is growing as cooperation occurs.This study analyzed the motivation of India to cooperate with African countries, why India is interested to cooperate, while on the other side of the western countries are reluctant to cooperate with African countries. This study uses the theory of international cooperation by KJ.Holsti, which explains the factors that encourage a state of international cooperation.Keywords: State, international cooperation, motivation, national interest